The 2nd SAU Annual Conference on Urological Research: SAU Conference Report - Liu, Xiaoqi; Li, Benyi (Serican Journal of Medicine, 2024)
The Serican Academy of Urology (SAU), established in the fall of 2022, is an international non-profit organization dedicated to uniting clinicians and basic scientists to address diseases related to the genitourinary tract. Prostate cancer, particularly castration-resistant prostate cancer (CRPC), remains a significant public health issue. The second annual SAU conference was held from June 13-16, 2024, at Banff Rocky Mountain Resorts, Alberta, Canada. Sponsored by MedChemExpress, ABclonal, and NovinoPath, and chaired by Dr. Xiaoqi Liu, the conference focused on the latest research in urological diseases. Topics included epigenetic regulation, novel treatment targets, bioinformatics, cancer etiology, progression and metastasis, the tumor microenvironment and immunotherapy, and overcoming resistance to existing therapies. Keynote addresses by leading scientists Drs. Jindan Yu and Qianben Wang emphasized the complexity of epigenetic and transcriptional regulation in prostate cancer. The Women’s Forum provided a platform to discuss career navigation and leadership development for women scientists in a predominantly male field. The conference concluded with a banquet, including an awards ceremony and committee reports.